Statement on the safety and efficacy of Shellac for all animal species. (16th April 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The additive Shellac is intended to be used as a technological additive (functional group: stabiliser) for all animal species. The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) assessed the data provided by the applicant in the technical dossier. During the course of the assessment, the need for additional information in order to be able to deliver an opinion on the safety and efficacy of this additive was identified and notified to the applicant. The information requested covered the description of the additive/efficacy, and safety of the additive. The applicant has failed to provide the additional information. Therefore, considering the data provided in the original dossier and the absence of response from the applicant to the request from EFSA, the FEEDAP Panel is not in a position to deliver an opinion on the safety and efficacy of the additive Shellac as a technological additive for all animal species.